Deriving The Standard Form Equation From The Vertex Form

The vertex form equation of a parabola is:

\[ y=\frac{(x-h)^2}{4p} + k\]

Expanding this:

\[\begin{gather} y=\frac{x^2-2hx+h^2}{4p} + k \\ y=\frac{x^2}{4p} - \frac{hx}{2p} + \frac{h^2}{4p} + k \end{gather}\]

We can write this as:

\[ y= \left( \frac{1}{4p} \right) x^2 + \left(- \frac{h}{2p} \right) x + \left( \frac{h^2}{4p} + k \right)\]

We can write the coeffecient as \(a\), \(b\) and \(c\):

\[ y= ax^2 + b x + c\]

This is the standard form equation of the parabola.

Styles

(uses cookies)